Bradykinin B1 receptor signaling triggers complement activation on endothelial cells - Lopatko Fagerström, Ingrid; Gerogianni, Alexandra; Wendler, Markus; Arvidsson, Ida; Tontanahal, Ashmita; Kristoffersson, Ann-Charlotte; Qadri, Fatimunnisa; Bader, Michael; Karpman, Diana (Frontiers in Immunology, 2025)
IntroductionThe complement and kallikrein-kinin systems (KKS) are both activated during vascular inflammation, and there are many known interactions between the two systems. This study investigated if KKS activation induced complement activation on endothelial cells, and if activation was dependent on bradykinin B1 receptor (B1R) signaling.MethodsKKS was activated in normal human serum by kaolin or activated factor XII (FXIIa). ADP-preactivated primary glomerular endothelial cells (PGECs) were incubated with serum, with or without kaolin or FXIIa, and with or without the B1R antagonist (R715) or the inositol triphosphate receptor (IP3R) inhibitor 2-aminoethoxydiphenyl borate (2-APB). Complement factors C3a, factor Ba and C5b-9 were evaluated by ELISA or immunoblotting. B1/B2 receptor double knock-out and wild-type mice were injected with lipopolysaccharide from E. coli B5:O55, to induce KKS activation.ResultsSupernatants from PGECs incubated with serum exposed to kaolin or FXIIa exhibited higher levels of Ba and C5b-9, which were significantly reduced in the presence of the B1R antagonist. Complement activation induced by FXIIa was also reduced in the presence of the IP3R inhibitor. Likewise, cell lysates showed higher levels of C3a and C5b-9 in the presence of kaolin and FXIIa, and complement activation was significantly reduced in the presence of the B1R antagonist. B1/B2 receptor double knock-out mice exhibited less C3 and C5b-9 deposition in glomeruli compared to wild-type mice.ConclusionThis study demonstrates that KKS activation contributes to complement activation on the endothelium by B1R signaling. Blocking the B1R may have a role in reducing complement deposition and its effects on the endothelium.